Innovation Achieved in Geomechanics Research in the BIGCCS Centre. (July 2017) - Cerasi, Pierre; Lavrov, Alexandre; Stroisz, Anna; Stenebråten, Jørn; Cuss, Robert; Wiseall, Andrew; Harrington, Jon; Graham, Caroline; Noy, David
Abstract: As part of the BIGCCS centre in Trondheim, Norway, a task in the sub-project dealing with CO2 sequestration looked at geomechanics and its significance for successful storage planning and operation. Innovation in this domain includes a laboratory activity, at SINTEF Petroleum Research, for examining thermal stress related fracturing risk in shale caprock and to test bonding strength between cement and rock by use of composite cement/rock plugs, whereas at BGS in Nottingham, UK, a bespoke shear rig to study permeability of faults as a function of stress history.